2018
DOI: 10.3390/jof4030101
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove-Associated Fungi: A Novel Source of Potential Anticancer Compounds

Abstract: Cancer is the second leading cause of death worldwide, and the number of cases is increasing alarmingly every year. Current research focuses on the development of novel chemotherapeutic drugs derived from natural as well as synthetic sources. The abundance and diversity in natural resources offer tremendous potential for the discovery of novel molecules with unique mechanisms for cancer therapy. Mangrove-derived fungi are rich source of novel metabolites, comprising novel structure classes with diverse biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 107 publications
(106 reference statements)
0
22
0
Order By: Relevance
“…The species in this genus are phytopathogenic, endophytic, and saprobic on different hosts (Hao et al, 2020). Antifungal bioactive compounds have been found in Nigrospora (Rana et al, 2019;Deshmukh and Prakash, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The species in this genus are phytopathogenic, endophytic, and saprobic on different hosts (Hao et al, 2020). Antifungal bioactive compounds have been found in Nigrospora (Rana et al, 2019;Deshmukh and Prakash, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This genus has also been isolated from B. gymnorrhiza and A. marina species in South Africa (Osorio et al, 2017). Deshmukh et al (2018) reported the presence of bioactive compounds in Lasiodiplodia with medical importance. From this study, the overall mean colonization frequency in the genus Aspergillus was found to be significantly higher compared to the other genera identified (P<0.05) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangroves grow in the salt-tolerant ecosystems with high biodiversity, and the abundance and diversity of mangrove resources provide the great potential for the discovery of new compounds [22]. In recent years, multiple potential anticancer compounds have been found from mangrove-derived endophytic fungi [22][23][24][25].…”
Section: Ivyspringmentioning
confidence: 99%